2021
DOI: 10.1021/acsanm.1c03055
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroadband Absorption and High-Performance Photodetection in Europium-Doped 2D Topological Insulator Bi2Se3 Nanosheets

Abstract: In the pursuit of materials with exceptional optoelectronic functionalities in the visible to mid-IR region, the topological insulators are very promising because they have unique Dirac-like surface states and high light-absorption properties. Herein, we report on a low-temperature, facile, solution-processable method for the synthesis of undoped and Eu-doped 2D layered Bi 2 Se 3 nanosheets (NSs) with exceptional optical functionalities. 2D geometry provides highly effective light absorption and efficient char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…As compared to the NS, the absorption edge for the QDs is blue-shifted due to the confinement effect. The bandgap of the as-synthesized samples were calculated using the following equation: 52 αhν 2 = A ( hν − E g )where α is the optical absorption coefficient, hν is the incident photon energy, and A is a constant. The Tauc plot of the samples is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As compared to the NS, the absorption edge for the QDs is blue-shifted due to the confinement effect. The bandgap of the as-synthesized samples were calculated using the following equation: 52 αhν 2 = A ( hν − E g )where α is the optical absorption coefficient, hν is the incident photon energy, and A is a constant. The Tauc plot of the samples is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both the devices show a fast photoresponse because of the superior carrier mobility of the 2D Bi 2 Se 3 NS. An increase in the growth time with the heterojunction formation might be due to the low carrier mobility caused by the high carrier concentration, as the electrons are transferred from the perovskite NCs to the Bi 2 Se 3 layers . Carrier trapping into deep subgap states is dominant in lead-based perovskite systems.…”
Section: Resultsmentioning
confidence: 99%
“…The narrow energy bandgap and the layered structure of Bi 2 Se 3 make it suitable for high-performance photodetectors and thermoelectric applications. Our recent work on Eu-doped 2D Bi 2 Se 3 showed high-performance photodetection over the visible to infrared region . However, there has been no study involving the 0D perovskite NCs and topological insulator.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many semiconductor nanostructures have exhibited negative PC, e.g. , as in p-type single-walled carbon nanotubes, 32 Bi-doped p-type ZnSe nanowires, 33 n-type InAs nanowires, 34 n-type InN thin films, 35 Bi 2 Se 3 nanosheets, 36 etc. Many theoretical predictions and experimental studies have been reported and debated to determine the origin of negative PC in such semiconductors.…”
Section: Introductionmentioning
confidence: 99%